A Study Against Colon Cancer Mechanism of Xanthium sibiricum Herba Based on Computer Simulation and Bioinformatics - Qi, Ying; Cai, Jia-Han; Deng, Qiu-Tong; Zeng, Yuan-Ning; Wang, Qiu-Hong (Combinatorial Chemistry & High Throughput Screening, 2024)
Introduction: Cancer is one of the leading causes of death worldwide, accounting for nearly one in six deaths in 2020. As a folk medicine, Xanthium sibiricum Herba (XSH) has been used many times in clinical practice for the treatment of various diseases. With the increasing number of cancer patients, there is a clinical need to find effective anti-cancer drugs. Aim: This study aims to explores the bioactivity and the anti-cancer mechanism of XSH. Methods: In this study, bioinformatics, network pharmacology, molecular docking, molecular dynamics simulation techniques, and apoptosis assay were used to explore the bioactivity and the anti- cancer mechanism of XSH. Results: Finally, seven active ingredients in XSH after the screening were obtained, the two most active compounds were β-sitosterol and aloe-emodin, and good anti-cancer activity of XSH was predicted. Discussion: Four core targets were obtained from the PPI network map, namely Caspase-3 (CASP3), Transcription factor AP-1 (JUN), Myc proto-oncogene protein (MYC), and cellular tumor antigen p53 (TP53). GO and KEGG analyses showed that the mechanism of XSH anti-cancer is mainly related to the apoptosis process, and the main signaling pathways are enriched in the p53 signaling pathway, Apoptosis, and MAPK signaling. The molecular docking and molecular dynamics simulation results showed that CASP3, JUN, MYC, and TP53 had a high affinity with β- sitosterol and aloe-emodin. Bioinformatics analyses demonstrated the importance of core targets. Apoptosis assay showed that XSH could significantly promote the apoptosis of cancer cells, and inhibit their proliferation and migration, especially colon cancer cells. Conclusion: This study uncovered the main active components, bioactivities, and potential targets of XSH, and further revealed the multi-component, multi-target, and multi-pathway mechanism of XSH for cancer treatment and promoting apoptosis.
Keywords: network pharmacology